MAJAS SIMILE DAN METAFORA DALAM LAGU-LAGU KARYA OFFICIAL髭男DISM - Driyawijaya, Randhyka Elga; Sudjianto; Bachri, Aep Saeful (Undiksha Press, 2023)
This research aims to describe the similes and metaphors in the songs by OFFICIAL髭男DISM. This research is a qualitative descriptive research. The two figure of speech that are the focus of this research are simile (直喩) and metaphor (隠喩). The data collection technique used in this research is the method of listening and recording, After the data is collected, the data is analyzed using the content analysis method. Researchers collected data from 13 songs and found 15 sentences of similes and 7 metaphors